PENGARUH BAHAN ORGANIK DAN KALSIUM TERHADAP STRUKTUR MIKRO TANAH - Uswah Hasanah (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
Soil microstructure as affected by organic matter and calcium was investigated by polarising microscope examination after three months incubation and by scanning electron microscopy (SEM) after one month incubation. Both polarising microscopy and SEM observations revealed an improvement of soil microstructure with the addition of cow dung and wheat straw.  Compared to the addition of dung, the straw amendment resulted in a greater microorganism diversity and lager porosity values.